Programa de actividades recreativas para mejorar la conciencia lateral de la escuela de formación deportiva de la Universidad Nacional de Loja, 2024. - Ramon Macas, Karen Anabell (2024)
The present curricular integration work was developed with the objective to improve the lateral awareness through recreational activities in 6–7-year-old children in the sports training school of the National University of Loja (Universidad Nacional de Loja). A mixed approach was used with a quasi-experimental design and a descriptive-correlational scope. Also, some methods such as deductive, inductive, analytical-synthetic, comparative and statistical were applied. Diagnostic instruments like Harris Test were carried out but with an adaptation, that is, selecting activities that agree with the research topic and an observation rubric with criteria aimed at the development of laterality. The sample was of ten children from the mentioned training school; and the results obtained through the instruments highlight the importance of the development of laterality in children, which benefits in their performance during their daily and sports activities. Based on the results, a recreational proposal was elaborated and then applied in a period of 10 weeks. In this proposal, recreational activities aimed at enhancing laterality in children were worked. After having been finished the application of the proposal, a Harris post-test with the same adaptation was executed, obtaining a significant improvement in laterality of children; and standing out the learning they gained and the ability to distinguish both hemispheres, which permits to form the basis of orientation and spatial structuring. Finally, the participation, abidance and commitment of children to participate in the class development is emphasized. This helps them to gain learning that motivates them to have an active life and interest in sports practice. Key words: lateral awareness, recreational activities, body outline, spatial structuring, orientation base.